Design of Wireless Variable Gesture Control For Mobile Devices (International Journal of Engineering and Computer Science, 2015)
Electromyography (EMG) is a technique for evaluating and recording the electrical activity produced by skeletal muscles. EMG is performed using an instrument called an electromyograph, to produce a record called an electromyogram. An electromyograph detects the electrical potential generated by muscle cell when these cells are electrically or neurologically activated. The signals can be analyzed to detect medical abnormalities, activation level, or recruitment order or to analyze the biomechanics of human or animal movement. In the proposed method we are using sensors instead of camera to sense and identify the gestures. Here we are using Accelerometers and surface electromyography (SEMG) sensors. These two sensors provide two potential technologies for gesture sensing. Accelerometers can measure accelerations (ACC) from vibrations and the gravity; therefore they are good at capturing noticeable, large-scale gestures.